2016
DOI: 10.2147/opth.s102683
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Scheimpflug imaging parameters between steep and keratoconic corneas of Caucasian eyes

Abstract: PurposeTo compare the keratometric and pachymetric parameters of healthy eyes with those affected by steep cornea and keratoconus (KC) using Scheimpflug camera.SettingBriz-L Eye Clinic, Baku, Azerbaijan.DesignA cross-sectional study.MethodsIn this study, 49 KC (Amsler–Krumeich stage 1) eyes and 36 healthy eyes were enrolled. A complete ophthalmic evaluation and a Scheimpflug camera scan were performed in every eye included in the study. Tomographic parameters such as parameters from the front and back cornea, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…However, the association of refractive errors with CKI, KI, and IHD indices was not significant. A review of the literature revealed no similar data in this regard, despite the study by Brizl et al [ 31 ], who showed the same data as ours. In patients without keratoconus (KC) disorder, the mean ISV in 36 eye samples was 21.83±8.03, their mean of IVA was 0.12±0.04, with a mean IHA of 5.02±4.29, and R min of 7.18±0.17.…”
Section: Discussionsupporting
confidence: 45%
“…However, the association of refractive errors with CKI, KI, and IHD indices was not significant. A review of the literature revealed no similar data in this regard, despite the study by Brizl et al [ 31 ], who showed the same data as ours. In patients without keratoconus (KC) disorder, the mean ISV in 36 eye samples was 21.83±8.03, their mean of IVA was 0.12±0.04, with a mean IHA of 5.02±4.29, and R min of 7.18±0.17.…”
Section: Discussionsupporting
confidence: 45%
“… Pentacam (Oculus Optikgerate GmbH, Wetzlar, Germany) Nil Henriquez et al, 2012 29 Peru Out-patients 151 28.4, 29.29 The study group was defined as keratoconus in both eyes, with the presence of clinical signs and topographic evaluation while the control group were subjects who had normal corneas in both eyes. Scheimpflug Imaging Analyzer (Pentacam; Oculus GmBH, Wetzlar, Germany) Not stated Huseynova et al, 2016 30 Azerbaijan Out-patients 85 23.77, 26.06 The study group were eyes with keratoconus while the control group were healthy corneas diagnosed according to Amsler–Krumeich criteria. 31 Pentacam HR (Oculus Optikgeräte GmbH, Wetzlar, Germany Not stated Koc et al, 2020 32 Turkey Out-patients 402 26, 24.8 The diagnosis of clinical keratoconus was defined by characteristic keratoconus signs in the anterior sagittal curvature maps while the control group was randomly selected from a database of age-matched candidates’ laser in situ keratomileusis (LASIK) for myopia (≤5.0 D) and myopic astigmatism (≤3.0 D) who had normal topographic, topometric and tomographic analysis and did not develop ectasia after at least 1-year follow-up.…”
Section: Resultsmentioning
confidence: 99%
“…The same ophthalmologist (Y.K) performed all the measurements. Topography images were taken using the Pentacam, which enabled images to be taken of the anterior and posterior surfaces of the cornea and iris, and of the anterior and posterior surfaces of the lens in a movable virtual eye (9) . After positioning the participant's head in a chin rest and head rest, the participant was asked to fixate on the center of the blue slit light.…”
Section: Evaluation Of Anterior Segment Parameters Usingmentioning
confidence: 99%